2017
DOI: 10.21273/hortsci12002-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vector Control and Foliar Nutrition on the Quality of Orange Juice Affected by Huanglongbing: Sensory Evaluation

Abstract: A 3-year study was undertaken to establish the effect of field nutritional sprays, combined with insecticide treatments or not against Asian Citrus psyllid, on the fruit quality of ‘Valencia’ orange trees affected by the greening disease Huanglongbing (HLB). Four replicated plots were harvested, juiced, and pasteurized. Nine to twelve trained panelists evaluated the juice using seven flavor, five taste, four mouthfeel and three aftertaste descriptors. There was little difference between treatments in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Nutritional treatments did not consistently result in less pathogen DNA for either variety (Baldwin et al, 2012a). The implementation of combined nutrient programs and insecticide treatments has been studied and the results suggest that the beneficial effect of increased orange juice quality may have been cumulative, only manifesting later on (Baldwin et al, 2017; Plotto et al, 2017).…”
Section: Huanglongbing Control and Mitigation Of Its Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional treatments did not consistently result in less pathogen DNA for either variety (Baldwin et al, 2012a). The implementation of combined nutrient programs and insecticide treatments has been studied and the results suggest that the beneficial effect of increased orange juice quality may have been cumulative, only manifesting later on (Baldwin et al, 2017; Plotto et al, 2017).…”
Section: Huanglongbing Control and Mitigation Of Its Symptomsmentioning
confidence: 99%
“…Juice made with these symptomatic, HLB-affected oranges had the most off-flavors, commonly described as “bitter,” “sour,” and “sour/fermented.” Higher bitterness and sourness in symptomatic fruit could be explained by higher levels of limonin and titratable acidity and with lower soluble solids content (Baldwin et al, 2010). A trained panel provided more insight into the various descriptors characterizing orange juice made with HLB-symptomatic fruit, with several negative descriptors regarding taste and flavor (astringency, tingling, harshness, bitterness, metallic-taste, low sweetness, saltiness/umami, musty, sourness/fermented, pungent/peppery, low citrusy taste; Tables 6, 7), usually due to an imbalance in the chemical composition in the affected fruit (Baldwin et al, 2010, 2012a, 2018; Plotto et al, 2010, 2017; Raithore et al, 2015; Dala Paula et al, 2018; Kiefl et al, 2018).…”
Section: Fresh Fruit and Orange Juice Quality Affected By Candidatus mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2014 and 2015, either I or I + N had the highest sugar and SSC/TA levels and lowest TA levels, although not always significantly different from C (TA) or N (SSC/TA), suggesting a cumulative effect of the treatments over the years. The chemical results are reflected in sensory results (Plotto et al, 2017) of the same samples, which were not consistent but showed that I or I + N were associated with positive orange juice characteristics (orange, fruit flavor, and sweetness), especially in 2015. Thus, use of insecticides (with or without nutritional treatment) seemed to improve flavor.…”
Section: Resultsmentioning
confidence: 85%
“…Sensory evaluation. Ten panelists trained and experienced at tasting citrus products (Plotto et al, 2010(Plotto et al, , 2017 gathered in two 1-h sessions to define descriptors that could characterize finger lime and to choose reference standards for three taste and five flavor attributes that matched those descriptors ( Table 2). Each reference standard was assigned a value that would correspond to a level that could be found in the finger lime samples.…”
Section: Fruit Quality Sensory Traits and Volatile Constituentsmentioning
confidence: 99%